Pengaruh Pandemi Covid-19 terhadap Evaluasi Pembelajaran Online Menggunakan Kurikulum 2013 pada SDN Pegadunga 03 Pagi - Magdalena, Ina; Septiani, Astrid Nur; Anisa, Tria Noer; Sabil, Fadel; Pitaloka, Nadia Rinjani (ARZUSIN, 2022)
COVID-19 pandemic has created new problems for the sustainability process in the education sector. This requires students to study from home to avoid exposure to the virus. The learning process from home certainly requires technology as a bridge to keep accessing the material. The constraints of an online-based learning system are considered to be a solution, as well as finding challenges from both the teacher and student side. The concept of learning at the elementary school level needs to be evaluated to improve the quality of teacher understanding and learning output in online-based classes. Mastery of learning resources, materials, and communication media are three elements that reinforce each other's learning methods. The research method used was interviews with representatives of teachers at SD Negeri Pegadungan 03 Pagi. The results of the study indicate that the design of blended learning or mixed learning is the solution. Blended Learning is a learning method that provides a combination of the use of technology, e-learning, and face-to-face learning. The blended learning model has a characteristic, namely all teaching and learning activities are carried out through a combination of online and face-to-face learning in delivering material. The blended learning method is one of the effective options to be implemented during the COVID-19 pandemic.